Interrelation of Reading Comprehension, Fluency, and Academic Achievement Among Grade 10 Learners - Castillo, Jason E. (Educative: Jurnal Ilmiah Pendidikan, 2025)
The Programme for International Student Assessment 2022 revealed the low performance of the Philippines in terms of literacy which means that Filipino learners are having difficulty comprehending the text that they are reading. This study examines the correlates and the factors that affect the reading comprehension performance of selected Grade 10 learners from the province of Rizal enrolled in SY 2024-2025 through different reading assessments. Descriptive-correlational method was used to identify the correlates and a qualitative discussion through case study to identify the factors. Results showed that only 14% (R²=0.140) of the variance is explained by the two predictors which indicates a weak correlation between the predictor and the outcome variable. It was also revealed that students under low performing reading level are having difficulty in reading comprehension because they are having difficulty in reading rate. This means that slow reading, which takes a lot of energy from them, can actually affect the way they understand the text. These findings suggest that there is a need for more intensified and contextualized reading assessments at the secondary level